2021
DOI: 10.1097/shk.0000000000001839
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alpha-1-Acid Glycoprotein in the Diagnosis and Treatment of Crush Syndrome-Induced Acute Kidney Injury

Abstract: Background: Crush syndrome (CS) is the most common cause of deaths following earthquakes and other disasters. The pathogenesis of CS has yet to be fully elucidated. Thus, clinical choice of ideal drug treatments for CS remains deficient. Methods and Results: In this study, we first evaluated the relation between extrusion force and the severities of CS. Rats were exposed to different extrusion forces: 1 kg, 3 kg, 5 kg, and 8 kg, respectively. Survival rates, crushed muscle tissue edema, serum biochemical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
1
4
1
Order By: Relevance
“…There is a significant weight difference between male and female rats of the same age; for example, an 8-week-old male rat typically weighs 280 to 330 g, while a female rat usually weighs 195 to 235 g. Through preliminary experiments, we determined that the ideal experimental animal is an 8-week-old male rat weighing 280 to 300 g. This ensures that there is sufficient muscle mass to induce AKI. Compared with our research, previous studies have indicated that a male rat weighing 220 to 240 g, when compressed on both lower limbs with a force of 5 kg for 16 h, has a 24 h survival rate of 80% (9). We believe that weight (muscle content) and age are the primary factors causing this significant discrepancy in survival rates.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…There is a significant weight difference between male and female rats of the same age; for example, an 8-week-old male rat typically weighs 280 to 330 g, while a female rat usually weighs 195 to 235 g. Through preliminary experiments, we determined that the ideal experimental animal is an 8-week-old male rat weighing 280 to 300 g. This ensures that there is sufficient muscle mass to induce AKI. Compared with our research, previous studies have indicated that a male rat weighing 220 to 240 g, when compressed on both lower limbs with a force of 5 kg for 16 h, has a 24 h survival rate of 80% (9). We believe that weight (muscle content) and age are the primary factors causing this significant discrepancy in survival rates.…”
Section: Discussioncontrasting
confidence: 77%
“…These discrepancies lead to variability in research outcomes, hindering the reproducibility of the model. To address these challenges, our team enhanced and iterated upon the foundation of the initial digital platform, independently developing a new generation multichannel intelligent small animal crush injury platform (9,10). We equipped it with an actuator specifically designed for small animals, a fixed position limiter, and a high-precision pressure sensor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged compression of limb muscles and subsequent decompression is essential in the development of crush syndrome (CS) [ 1 ], including hyperkalemia, metabolic acidosis, hypovolemic shock, acute kidney injury, and disseminated intravascular coagulation [ 2 ]. The sequential damage in the kidney after crush injury is not the unique dysfunctional organ [ 3 ]. It has been proved that the secondary damage in the lung [ 4 6 ], heart [ 7 ], and liver [ 8 ] contributes to multiple organs failure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study of renal protection utilizes a rodent model of crush injury. With this model, investigators from the Institute of Disaster Medicine in China identified proportional increase in serum potassium, creatine kinase, blood urea nitrogen, creatinine and myoglobin at 12 to 24 h after crush trauma (19). From this reproducible injury model, the authors evaluated protein profiles in study animals.…”
mentioning
confidence: 99%